(untitled) (TEL Tempo, Espaço e Linguagem, 2021)
This study aims to investigate how the main authors of the historiography of Independence analyzed the Liberal Revolution of Porto. This movement was for a long time articulated as an antecedent chapter of Brazilian independence, generating the need for a better understanding of its historiography in order to understand the permanence of this interpretation.